Persepsi Mahasiswa Terhadap Penerapan Metode Gamifikasi Bertema Harry Potter pada Mata Kuliah Konsep Dasar Bahasa Indonesia Sekolah Dasar - Janattaka, Nugrananda; Satria, Aditya Pringga; Oktaviarini, Nourma (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to explore the method of applying gamification using the Harry Potter theme from the perspective of students, and explore the benefits of the gamification method using the Harry Potter theme from the perspective of students. The research method is qualitative with the instruments used being questionnaire sheets, interview sheets and documentation. The data collected is analyzed through several processes, namely data reduction, data presentation, and conclusion drawn. Based on the results of the questionnaire and interview, it can be concluded that 80% of students know the gamification method, then 90% of students stated that the Harry Potter-themed gamification method can increase student motivation, then 90% of students stated that the Harry Potter-themed gamification method can help students understand the material, 88% of students also stated that lecturers' innovations in designing Harry Potter-themed games, and 88% of students stated that gamification can change students' attitudes during Learning